Constraints Faced by Paddy Farmers in Adoption of Climate Smart Agricultural Practices: A Comparative Study - Mishra, Ayush; Malik, Joginder Singh; Bhavesh (Indian Journal of Extension Education, 2024)
The study was conducted in 2023 to identify the major constraints faced by paddy farmers in the adoption of climate-smart agricultural practices in the eastern climactic zone of Haryana. The data was collected with a structured interview schedule from two groups of villages namely climate-smart and non-climate-smart villages, randomly selected 120 respondents from four blocks of Karnal and Kaithal districts. The constraints were divided into three categories i.e., economic constraints, socio-personal constraints, and technological constraints. The analysis revealed that technical constraints such as lack of awareness about climate-smart agricultural practices, lack of training, and complexity of climate-smart practices were the major barriers to the adoption of climate smart agricultural practices among the farmers of non-climate smart villages whereas, economic constraints such as increased cost of paddy production, higher initial investments in inputs and lower paddy yields were the most serious constraints faced by farmers in climate smart villages. Furthermore, it was observed that, while there was not much difference in socio-personal and economic constraints faced by both groups of respondents, however, respondents from non-climate smart villages faced a significantly higher degree of technical constraints as compared to the respondents from climate smart villages.